MODEL MANAJEMEN MUTU BERBASIS KEPATUHAN REGULASI UNTUK PENINGKATAN KINERJA PELAYANAN DI TERMINAL UNTUK KEPENTINGAN SENDIRI (TUKS) WILAYAH KERJA KSOP PEKANBARU - Gradina Nur Fauziah; Fery Kurniawan; Andi Nurhidayanti (UNIMAR AMNI Semarang, 2026)
The purpose of this conceptual study is to formulate a quality management model for port services at Terminals for Own Interest (TUKS), focusing on regulatory compliance aspects, based on an in-depth analysis of the Cooperation Agreements (PKS) between the Port Authority and Harbour Master’s Office (KSOP) Class II/III Pekanbaru and various TUKS operators. TUKS is a crucial element in the national logistics chain, whose operations are highly dependent on the legal framework stipulated in the PKS, covering aspects of maritime safety, security, and environmental protection (Angkasa & Darmawan, 2024). The method used is qualitative document analysis (PKS) to identify primary quality variables: Regulatory Compliance and Partnership Sustainability. The analysis results show that the PKS serves as a quality instrument that obligates TUKS operators to meet minimum operational standards. The proposed model is the